The Government Effort in Improving Healthcare Access in Rural Communities Based On Law - Rio Dwi Pradana Putra; Zainul Ibat; Achmad Romdhan Syah; Aceng Wiantono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In health law, obtaining adequate services and facilities is a right that the Indonesian people must obtain. However, rural areas tend to have inadequate services and facilities due to many factors. The health condition in this village is certainly not in accordance with the applicable health laws. Therefore, researchers are interested in analyzing government efforts to improve health services and facilities in rural areas related to health law. The results obtained are that many areas have not received adequate health services and facilities. So far, the government has made efforts to improve these health services and facilities; it's just not optimal and more effort is needed so that all rural communities can feel the results obtained.